IMPLEMENTASI MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS ANALISIS SWOT (STRENGH, WEAKNESS, OPPORTUNITY AND TREAT) DI MADRASAH IBTIDAIYAH UNGGULAN AL AZHAR - Adi Suwarno, Suparjo (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2024)
The aim of this research is to describe the SWOT-based financing management of educational institutions by implementing concrete steps in the process so that it will produce healthy and accountable financing management. This research used a qualitative research method known as a case study. Data collection methods use observation techniques, interview techniques and documentation. Next, the data obtained was then analyzed using the Miles-Huberman and Saldana interactive data analysis model. Data validity uses method triangulation and source triangulation. The research results showed that financial management of educational institutions using SWOT analysis will produce financial management that is transparent, accountable and able to predict problems that may occur in the future.